Physical fitness and anthropometric profile of students referees of the Ceará school’s football referees - da Silva, Magna Leilane (2012)
This study aimed to determine the anthropometric and physical fitness level of students in the referees school Alzir Brilhante EAAB / FCF (Cearense Football Federation). The sample was composed of 29 students with a mean age of 23.8 ± 0.0 years, weight 73.6 ± 14.5 cm and height of 1.75 ± 0.1 m. Anthropometric variables were measured: weight, height, body fat percentage and body water, by bioelectrical impedance method. Flexibility was measured using the Bank of Wells, abdomen muscular endurance through the abdominal strength test repetitions for one minute and aerobic capacity by the Cooper test performance. After analyzing the data it was found that the body fat percentage of students was 20.9 ± 7.4%. Seventy nine (79%) percent of students had a level of flexibility below the good level. Only 10% of students achieved the concept to fit in accordance with the rate established by FIFA in Cooper test. Based on these results it is suggested that the Ceara’s referees school pass the offer to its students physical conditioning programs associated with nutritional guidance to improve the profile of these subjects.